An effective framework for total quality management in information systems building - Masela, Piet Timothy (My University, 2006)
Business processes in all sectors of the business community require information to achieve the missions of their organisations. The quality of the information is directly related to the quality of the application system which process or produce such information. During application systems development, the project manager should consciously gather the application owner’s quality requirements, and ensure that those requirements are built into the application which is delivered at the conclusion of the development project. The specified quality requirements should be measurable to ensure that their presence can be verified in the end product. This report uses quality attributes obtained from the International Standard (ISO) 9126 Software Evaluation Framework, to specify these requirements and to verify their achievement. This research found that there is a consensus among application system owners and project managers on the importance of quality attributes as an evaluation tool of the quality of an application system. In the quest for quality, the starting point should be gathering of quality requirements and their correct interpretation.
There are 5 files which have been withheld at the author's request. Master of Commerce - Commerce
Keywords: management; information systems; building